(untitled) (Research, Society and Development, 2022)
This study aimed to report an experience of continuing health education developed with nurses from long-stay institutions for the elderly, about the role and participation of the family in the lives of institutionalized elderly people. This work consists of a descriptive study, with a qualitative approach, of the experience report type, developed in the months of August and September 2021, with nurses working in Long-stay Institutions for the Elderly in the municipalities of the Vale do Jaguari region, through of an EPS that took place in three meetings, online through the Google Meet platform. In this article, the first and third meeting will be discussed. The first meeting was held through a dynamic presentation with nurses and a survey of possible themes to be worked on based on the nurses’ needs. The third meeting was about the role and participation of the family in the lives of institutionalized elderly people. It is concluded that the continuing education in health developed with nurses who work with the elderly allowed the participants to make several reflections on the importance of the role of the family for institutionalized people. Still, this experience contributed to strengthening the link between the academic community and institutionalized elderly service, aiming at the quality of care offered to the elderly population.